Breast cancer in Finistère, France: epidemiological description and tendencies over a 10-year period (2000-2009) according to pathology data - Lietard, Claire; Conan, Virginie; Le Fur, Jean-Marie; Minot, Jean-Pierre; Le Callonec, Marie; Brisseau, Cyrille; Saliou, Philippe; Lejeune, Benoist; Lagarde, Nicole; Garlantézec, Ronan (Annales de pathologie, 2013)
The aim of this study was the description of breast carcinoma over a 10-year period according to pathology data. Descriptive epidemiological study based on data collection of pathological code ADICAP (injury, organ, and applied technical), histological, hormonal, node and administrative data. From January 1st 2000 to December 31st 2009, 6186 women living in Finistère have had a diagnosis of invasive breast carcinoma. The incidence rate involved from 125 per 100,000 women to 136 in 2009. Average age to the first diagnosis was 61.4 ± 13.6; class of age with the more important incidence rate was for the 50-74 years old. The different histological subtypes varied over the period (P<0.0001). Tumour's size was notified for more than 75% in the whole period of the study. The average size evolved significantly over the period (P<0.0001 from 23.5mm [± 18.4] in 2000 to 21.02 [± 16.2] in 2009, particularly after 2003 [P<0.0002]). The grade status (SBR, MSBR and Elston Ellis) showed a trend to the gravity decrease over the period (respectively P=0.03 [r(2)=-0,04]; P<0.0001 [r(2)=-0.10]; P<0.0001 [r(2)=-0.08]). Our results confirm the interest of pathology database for the description of invasive breast cancer.